Induction of Lipid Metabolic Enzymes during the Endoplasmic Reticulum Stress Response in Plants - Shank, Karin J. (American Society of Plant Physiologists, 2001)
The endoplasmic reticulum (ER) stress response is a signal transduction pathway activated by the perturbation of normal ER metabolism. We used the maize (Zea mays) floury-2 (fl2) mutant and soybean (Glycine max) suspension cultures treated with tunicamycin (Tm) to investigate the ER stress response as it relates to phospholipid metabolism in plants. Four key phospholipid biosynthetic enzymes, including DG kinase and phosphatidylinositol (PI) 4-phosphate 5-kinase were up-regulated in the fl2 mutant, specifically in protein body fractions where the mutation has its greatest effect. The third up-regulated enzyme, choline-phosphate cytidylyltransferase, was regulated by fl2 gene dosage and developmental signals. Elevated accumulation of the fourth enzyme, PI 4-kinase, was observed in the fl2 endosperm and soybean cells treated with Tm. The activation of these phospholipid biosynthetic enzymes was accompanied by alterations in membrane lipid synthesis and accumulation. The fl2 mutant exhibited increased PI content in protein body membranes at 18 d after pollination and more than 3-fold higher triacylglycerol accumulation in the endosperm by 36 d after pollination. Incorporation of radiolabeled acetate into phospholipids in soybean culture cells increased by about 30% with Tm treatment. The coordinated regulation of ER stress related proteins and multiple components of phospholipid biosynthesis is consistent with signaling through a common pathway. We postulate that the plant ER stress response has an important role in general plant metabolism, and more specifically in integrating the synthesis of protein and lipid reserves to allow proper seed formation.